(NwYSOKOTEMPERATURNYJ \LEKTROLIZ GAZOW (B/s - (NpERFILXEW(B, (NmIHAIL wASILXEWI^s; (NdEMIN(B, (Na(B.(Nk(B.s; (NkUZIN(B, (Nb(B.(Nl(B.s; (NlIPILIN(B, (Na(B.(Ns(B.s; (NkARPA^EW(B, (Ns(B.(Nw(B.s; (NiN(B-(NT \LEKTROHIMII uRALXSKOGO OTD(B. (Nan sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B. (NW KONCE GLAWs
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
(Nan sssr(B, (NuRAL(B. (NOTD(B-(NNIE(B, (NiN(B-(NT \LEKTROHIMIIs
Keywords: (NbAZY (B- (N|LEKTROLIZs